Resumption of traditional drive hunting of dolphins in the Solomon Islands in 2013. Issue 5 (May 2015) - Oremus, Marc; Leqata, John; Baker, C. Scott
Abstract : The 'drive hunting' of dolphins has a long history in the Solomon Islands, specifically at the island of Malaita. In 2010, the most active village, Fanalei, suspended hunting in exchange for financial compensation from an international non-governmental organization but resumed hunting again in early 2013. Here, we report on a visit to Fanalei in March 2013 to document the species and number of dolphins killed in the renewed hunting. Detailed records for the 2013 hunting, up to the time of our visit, included at least 1500 pantropical spotted dolphins ( Stenella attenuata ), 159 spinner dolphins ( Stenella longirostris ) and 15 'bottlenose' dolphins, probably Tursiops truncatus . Molecular identification confirmed two of the species, pantropical spotted and spinner dolphins. A summary of all available records from 1976 to 2013 documented a minimum total of 15 454 dolphins killed by the Fanalei villagers alone. We also found the local price of a dolphin tooth had increased from about US0.14 (SBD1) in 2004 to about US0.70 (SBD5) in 2013. The large number of dolphins killed and the apparent incentive for future hunting offered by the increasing commercial value of teeth, highlight an urgent need to monitor hunts and assess the abundance and trends in local populations.